PENGARUH MOTIVASI DAN KOMITMEN ORGANISASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PERUSAHAAN INDOMARCO PRISMATAMA KOTA BANDA ACEH - Yuddha, Ayi Satria; Gunawan, Gunawan (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2024)
The purpose of this research is to determine the magnitude of the influence of motivation and organizational commitment on the work productivity of the Indomarco Prismatama Company, Banda Aceh, both simultaneously and partially. This research uses quantitative methods with a population of 35 employees. The sampling technique is a saturated sample (census method), where all employees are used as samples. Data collection was carried out by distributing questionnaires to respondents and processed using SPSS version 29.0 statistical tools. Hypothesis testing uses multiple linear regression analysis, f test (simultaneous) and t test (partial) to determine the effect of the independent variable on the dependent variable at a 95% confidence level. The results of the research show that partially motivation has a positive and significant effect on employee work productivity with a value of tcount (5.441) greater than ttable (2.037) with a significance value of p value 0.010 and organizational commitment has a positive and significant effect on employee work productivity with a value of tcount ( 3.011) is greater than the t table (2.037) with a significance value of p value 0.001. Simultaneously, motivation and organizational commitment have a positive and significant influence on work productivity with a significance p value of 0.020 with fcount (5.170) greater than ftabe1 (3.285). It can be concluded that both partially and simultaneously motivation and organizational commitment have a positive and significant effect on the work productivity of Indomarco Prismatama Company employees in Banda Aceh.